Survival outcomes and prognostic factors of squamous cell carcinomas arising from sinonasal inverted papillomas: a retrospective analysis of 120 patients. Issue 11 (12th August 2019) - Li, Yunxia; Wang, Chengshuo; Wang, Ru; He, Shizhi; Feng, Ling; Ma, Hongzhi; Lian, Meng; Shi, Qian; Zhong, Qi; Chen, Xiaohong; Fang, Jugao; Zhang, Luo
Abstract : Background: This study aimed to analyze the prognostic factors and survival outcomes of squamous cell carcinoma (SCC) originating from sinonasal inverted papillomas (IPs), based on data from a single institution. Methods: The data from 120 patients treated at the affiliated Beijing Tongren Hospital, Capital Medical University, for SCC originating from sinonasal IPs between 2005 and 2018 were retrospectively reviewed. Data related to demographic features, tumor characteristics, treatment modality, and clinical outcomes were collected. Survival data were investigated using the Kaplan‐Meier method, Cox regression analysis, and the nomogram model predictive of survival probabilities. Results: Among 1034 patients with sinonasal IPs, 120 patients (11.6%) with malignancy were identified. The overall survival (OS) and disease‐free survival (DFS) rates at 5 years were 56.0% and 42.3%, respectively. Multivariate analysis showed that synchronous tumors and tumor stage were independent predictive factors for the risk of mortality (hazard ratio [HR], 1.954; 95% confidence interval [CI], 1.022‐3.737, p = 0.043; HR, 1.737, 95% CI, 1.095‐2.770, p = 0.020, respectively). The surgical margin was another important independent predictor, with patients with negative margins demonstrating a more than 2‐fold improved survival compared to those with positive margins (HR, 2.095; 95% CI, 1.031‐4.243; p = 0.041). Conclusion: The main factors affecting the prognosis and outcomes were synchronous tumors, advanced tumor stage, and positive surgical margins. These findings highlight the importance of tumor biology and early detection in patient outcomes. In addition, risk factors should be taken into consideration during treatment planning and subsequent tumor surveillance.